Advanced laser-induced breakdown spectroscopy-based qualitative analytical methodologies for food and plant-related applications - Casian Plaza Fernando Alexander; Janovszky Patrick; Palásti Dávid Jenő; Kondak Selahattin; Kolbert Zsuzsanna; Galbács Gábor; 30th International Symposium on Analytical and Environmental Problems Szeged 2024. október 7-8. (University of Szeged Szeged, 2024)
There is a growing need for the non-destructive, simple, cost-effective and fast inspection of products in the agricultural and food industry for quality control. Laser-induced breakdown spectroscopy (LIBS) has a great potential in this application. This research was focused on three main methodologies: a) the qualitative discrimination of plants in a fast, non-contact and microdestructive way; b) method development of spatially resolved LIBS elemental mapping of plant species for nanoparticles (NPs) detection; and c) the identification of harmful contaminants (e.g. pesticides, heavy metals, NPs).
Keywords: Természettudományok; Kémiai tudományok